MANAGEMENT OF RETAILING SERVICE COMPETITIVENESS - Oksana Valeryevna Khlopenko (Advanced Engineering Research)
Some classifications of retailing services are listed and evaluated. On this basis, an updated notion of the service structure is proposed. It includes four components: distributive services, commercial services, sales support, merchandising. At that, a special role of merchandising in the competitiveness support for the modern retail enterprise is marked. The updated structure of the retailing service permits to single out its competitiveness factors. Special attention is paid to the strategic management of the retail enterprise competitiveness within which strategic solutions on four structural components are developed. Conceptual approaches to the appropriate strategy development are presented. They are based on the building of the updated retail trade structure, as well as on the identification of the competitiveness factors of the services.